Police reform in Scotland: What can we learn from the experiences of front-line officers? - Hail, Yvonne (2020)
Little is known about how front-line police officers navigate major structural reforms within their organization. The findings presented in this paper were collected as part of the first ever empirical study of the newly created Police Service of Scotland between October 2013 and June 2014. The findings discussed here are pertinent to the wider academic literature in that they fill the current gap in knowledge on how front-line police officers experience major structural reforms at a police operational level; by exploring the ways, if any, reform impacted on the routine delivery of local policing. This paper focuses on three main themes which emerged from the analysis of 68 interviews conducted with a stratified sample of serving police officers; front-line police officers, their supervisors and managers across two geographically distinct case study areas in Scotland. The paper highlights police officers' concerns around a lack of front-line involvement in either the planning or implementation of reform, the pace at which the changes associated with reform were rolled out and the internal communication processes adopted throughout the reform journey, all of which they claim impacted negatively on their daily routines. This unique data was collected using a variety of qualitative and ethnographic research approaches including non-participant observations, walking interviews, documentary analysis and semi-structured interviews at the precise time major structural reform was being implemented across Scotland